Detection of queuosine and queuosine precursors in tRNAs by direct RNA sequencing - Sun, Yu; Piechotta, Michael; Naarmann-de Vries, Isabel S.; Dieterich, Christoph; Ehrenhofer-Murray, Ann E (Nucleic acids research, 2023)
Queuosine (Q) is a complex tRNA modification found in bacteria and eukaryotes at position 34 of four tRNAs with a GUN anticodon, and it regulates the translational efficiency and fidelity of the respective codons that differ at the Wobble position. In bacteria, the biosynthesis of Q involves two precursors, preQ0 and preQ1, whereas eukaryotes directly obtain Q from bacterial sources. The study of queuosine has been challenging due to the limited availability of high-throughput methods for its detection and analysis. Here, we have employed direct RNA sequencing using nanopore technology to detect the modification of tRNAs with Q and Q precursors. These modifications were detected with high accuracy on synthetic tRNAs as well as on tRNAs extracted from Schizosaccharomyces pombe and Escherichia coli by comparing unmodified to modified tRNAs using the tool JACUSA2. Furthermore, we present an improved protocol for the alignment of raw sequence reads that gives high specificity and recall for tRNAs ex cellulo that, by nature, carry multiple modifications. Altogether, our results show that 7-deazaguanine-derivatives such as queuosine are readily detectable using direct RNA sequencing. This advancement opens up new possibilities for investigating these modifications in native tRNAs, furthering our understanding of their biological function.
Online vorab veröffentlicht: 9. Oktober 2023
Gesehen am 27.11.2023